Running performance, not anthropometric factors, is associated with race success in a Triple Iron Triathlon - Knechtle, B.; Kohler, G. (British Journal of Sports Medicine, 2009)
Objectives: To investigate the influence of anthropometric parameters on race performance in ultra-endurance triathletes. Design: Descriptive field study.